2014
DOI: 10.1186/1471-2369-15-98
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan chewing gum on reducing serum phosphorus in hemodialysis patients: a multi-center, randomized, double-blind, placebo-controlled trial

Abstract: BackgroundHS219 (40 mg chitosan-loaded chewing gum) is designed to bind salivary phosphorus as an add-on to available phosphorus binders. We performed a randomized, placebo-controlled, double-blind study to evaluate the efficacy and safety of HS219 in hemodialysis (HD) patients with hyperphosphatemia as an add-on to phosphorus binders.MethodsSixty-eight HD patients who were maintained on calcium carbonate (n = 33) or sevelamer hydrochloride (n = 35) were enrolled. The primary end point was a change in serum ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
7
2
Order By: Relevance
“…The chitosan-loaded chewing gum HS219 does not affect serum and salivary phosphorus levels in Japanese HD patients with hyperphosphatemia. These findings do not support previous findings that 20 mg of chitosan-loaded chewing gum reduces serum and salivary phosphorus levels [63].…”
Section: Salivary Phosphorus Binding Agentscontrasting
confidence: 70%
“…The chitosan-loaded chewing gum HS219 does not affect serum and salivary phosphorus levels in Japanese HD patients with hyperphosphatemia. These findings do not support previous findings that 20 mg of chitosan-loaded chewing gum reduces serum and salivary phosphorus levels [63].…”
Section: Salivary Phosphorus Binding Agentscontrasting
confidence: 70%
“…These results were in (9) who found that serum phosphate significantly decreased during the first weeks of chewing chitosan gum in ESRD patients and returned to baseline after discontinuing the chewing gum. Our results were not in agreement with Akizawa T et al,2014 (10) who found that chewing gum and expelling saliva does not affect serum and salivary phosphorus levels in Japanese HD patients with hyperphosphatemia. On the other hand, our study showed that group patients (CKD patients stage 3 or 4 who received calcium acetate and pilocarpine) had increased salivary urea, creatinine, and phosphorus levels when compared with control group (CKD patients stage 3 or 4 who received calcium acetate only) with p value <0,06 for all comparisons, and also had decreased serum urea, creatinine and phosphorus levels when compared with control group with p value <0,03 for all comparisons.…”
Section: Discussioncontrasting
confidence: 56%
“…37 It is similar to sevelamer; however; it absorbs less water thus showing less swelling and higher fluidity than sevelamer. 16,17 In phase 3 studies conducted in Japan, bixalomer was shown to be as effective as sevelamer for the management of serum PO 4 levels with 72.2% of subjects achieving target PO 4 levels, between 3.5 and 6.0 mg/dL as compared with the sevelamer group, which only had 68% achieve those levels. Additionally, the percentage of GI adverse events was significantly lower in the bixalomer group with 29.1% reporting events versus 47.3% in the sevelamer group.…”
Section: Calcium-based Bindersmentioning
confidence: 99%
“…14,15 Bixalomer another nonmetal, nonabsorbable is available in Japan. 16,17 Velphoro Ò (sucroferric oxyhydroxide), a chewable, ironbased binder with no significant change on iron parameters, 18 and Auryxia Ò (ferric citrate) an iron-based binder with clinically and statistically significant increases in iron parameters. 19 Additionally, studies have looked into once daily dosing of sevelamer, the use of niacin/nicotinamide, and the use of a salivary phosphate-binding chewing gum to improve serum PO 4 levels.…”
mentioning
confidence: 99%